2014
DOI: 10.1097/ftd.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine (Total and Unbound) and AGP Concentrations After Transversus Abdominis Plane Block for Analgesia After Abdominal Surgery

Abstract: Although the total ROP concentrations approached or exceeded reported neurotoxicity thresholds, no patients had unbound ROP concentrations approaching the unbound toxicity threshold, nor showed any signs or symptoms of toxicity. This result was consistent with changes in protein binding to alpha-1 acid glycoprotein after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…This review identified 15 studies investigating systemic concentrations of LA after TAPB and RSB. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] It is the first systematic review to collate primary studies assessing the safety of LA after anterior abdominal wall blocks. Although a significant number of patients in the included trials exceeded potentially toxic thresholds (33 of 381 patients) of LA as defined by previous clinical trials and case studies, only three patients reported mild symptoms of LA systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review identified 15 studies investigating systemic concentrations of LA after TAPB and RSB. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] It is the first systematic review to collate primary studies assessing the safety of LA after anterior abdominal wall blocks. Although a significant number of patients in the included trials exceeded potentially toxic thresholds (33 of 381 patients) of LA as defined by previous clinical trials and case studies, only three patients reported mild symptoms of LA systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, no significant differences of C max were observed between various truncal blocks using the same LA. The RSB is achieved by LA agent administrated to block the terminal branches of the ninth, 10th, and 11th intercostal nerves and 200 mg 22 50 mg 21 100 mg 21 150 mg 21 201 mg 18 199 mg 20 (L) 400 mg 24 (LB) 100 mg 25 100 mg 30 131 mg 32 provides sensory block to the midline of the abdomen. 48 Anatomical studies demonstrate the relationship between the location of LA administration and the desired region of anaesthesia, where exposure to large vascular surface areas provides ideal conditions for rapid LA systemic absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of bilateral TAP block catheters found that a 10 mL⋅h −1 infusion of 0.2% ropivacaine, initiated 30 minutes after a loading dose of 100 mg ropivacaine per side, resulted in a continuing rise in plasma concentration up to 48 hours. 49 There was wide interindividual variability, with a large number of subjects having total concentrations exceeding the toxic threshold. However, it was reassuring to note that the unbound ropivacaine concentration was much lower and remained well below toxic threshold.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In a previous study, an intraoperative 40 mL bolus dose of 0.5% ropivacaine did not show any toxicity issues. In this study, the mean (±SD) peak plasma total (bound plus unbound) ROP concentration (C max ) was 2.09 (±0.81) mg/L and unbound ropivacaine concentration was 0.044 (±0.016) mg/L 14. We also realized that in the IBG, the 8-hourly visits by APS staff might have an additional placebo effect; thus leading to a performance bias.…”
Section: Discussionmentioning
confidence: 65%